Deprived children in Ireland: Characterising those who are deprived but not income-poor - Slevin, Eva; Russell, Helen; Maître, Bertrand (ESRI, 2026)
This report examines child deprivation in Ireland. It focuses on children who experience deprivation but are not classified as at-risk-of-poverty (AROP). As a result, they fall outside the official consistent poverty measure, which is a combined measure of AROP and deprivation. The report uses data from the Survey of Income and Living Conditions (SILC) to investigate the composition and characteristics of this group. The report underscores the need for comprehensive policies to improve living standards for vulnerable families.